Kinship and Social Groups A Modular Approach. Cultural Anthropology / Peter Kassebaum. - Kassebaum, Peter (Distributed by ERIC Clearinghouse, 1985)
Designed for use as supplementary instructional material in a cultural anthropology course, this learning module introduces commonly employed terms used in the study of kinship and social groups. Conceptual categories used to describe the social structures of society are defined first, including culture, material culture, nonmaterial culture, society, primary groups, secondary groups, aggregation, and social categories. Kinship analysis is described next, with focus on the following concepts: (1) the nuclear and extended family; (2) marriage, including monogamy, polygamy, polygyny, polyandry, sorral polygyny, and fraternal polyandry; (3) residence, including exogamy, endogamy, matrilocal, patrilocal, and neolocal patterns; (4) bride price, dowry, and suitor service; (5) descent, including kindred, and bilateral, unilineal, patrilineal, and matrilineal descent; (6) clans, phratries and moieties; and (7) leadership, including matriarchal, patriarchal, egalitarian, matricentric, patricentric, and egalicentric models. Finally, kinship diagramming is covered. Performance activities covering the module's content are appended. (LAL)